Aktualisasi Nilai-Nilai Kepemimpinan Astha Brata Untuk Mewujudukan Profil Pelajar Pancasila Melalui Sekolah Penggerak - Atik Dwi Kurniasih (Universitas Sebelas Maret, 2022)
To realize the Pancasila Student Profile, the Ministry of Education and Culture, Research and Technology issued one of the Independent Learning Program policies, namely the